THE INFLUENCE OF PRESSURE, PROCRASTINATION AND ABILITY ON AUDITOR ACADEMIC CHEATING DURING INTERNAL TRAINING FAUD BEHAVIOUR - Tavis, Sean Ivander; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2024)
This thesis addresses a significant research gap by investigating the influence of pressure, procrastination, and ability on academic cheating among auditors during internal training, specifically in online settings. Previous literature lacks comprehensive studies in this context, making this research essential for understanding cheating behaviors in the auditing profession. The study's practical relevance lies in informing organizations providing internal training to auditors, enabling the development of more effective programs and ethical guidelines. Addressing academic cheating is crucial for upholding auditors' integrity, maintaining trust within the industry, and improving educational methods. This research contributes to the academic literature on ethics, training, and professional development while providing insights for policymakers and professional bodies to establish guidelines against cheating. Through rigorous methodology including validity, reliability, normality, multicollinearity, and autocorrelation tests, the study confirms that pressure, procrastination, and ability significantly influence auditor academic cheating. The multiple linear regression analysis reveals that all three variables have positive effects on cheating behavior. The findings, supported by a strong R-squared value of 0.712, indicate that 68.5% of auditor academic cheating is explained by pressure, procrastination, and ability. The research results show that that pressure, procrastination have all demonstrated a positive influence on auditor academic cheating behavior perceived ability does not significantly influence on auditor academic cheating behaviour but still has positive correlation. So this research emphasizes the importance of addressing these factors in training programs to encourage ethical behavior and professionalism in the audit profession.